Dylematy i doświadczenia funkcjonowania sejmowych komisji śledczych w Polsce - Krawczyk-Antońska, Żaneta; Jaruga, Kinga (Political Preferences, 2013)
The practice of political life often indicates that the implementation of the control function is one of the most important elements of the Polish parliament's competency. The possibility of appointing parliamentary commit- tees of inquiry guaranteed by the Constitution is undoubtedly the clearest, and the most spectacular form of its exercise. However, It would seem that the clear form of the accepted political solutions does not eliminate various doubts of procedural, political and legal nature relating to their functioning. It is no wonder that parliamentary committees of inquiry, becoming media phenomena, are increasingly seen as a weak link in the process of political reality. The main objective of this paper is to show the form and the position of committees of inquiry, arising not only from the accepted legal and constitutional solutions, but also non-formal conditions shaped by political, media as well as social culture. The intention of the authors is an attempt to present the actual importance of parliamentary committees of inquiry in view of the perception of their activities by the electorate of particular parties.